Por que o público não é maior? causas sobre a ausência de consumidores nos estádios da Cidade de São Paulo - César, Fábio Soares (2015)
The industry of world sport, especially football, has won every year an important place in the world economy. On the other hand, the Brazilian football has a distinct reality of European countries where the average occupancy of stadiums rates exceed 80%, as in our country the average occupancy rate in our stadiums does not exceed 40%. In this scenario, the objective is to identify and analyze the factors that influence in the absence of consumers to professional football matches in stadiums in São Paulo. The theoretical framework covered the following concepts: consumer behavior, the sports consumer, stadiums and arenas as production tools and sports consumption and the absence at sporting events. The study addressed consuming people of football, having sympathy or cheer for a club and that at some point attended professional soccer matches in one of the stadiums and arenas in the city of São Paulo. We opted for the city of São Paulo for their representation in the national football scene and this having four professional football teams that regularly compete for championships at regional and national level in the main divisions of Brazil. This study adopted a quantitative approach, such as data collection instrument used a questionnaire survey, involving such consumers into three distinct periods (before, during and after the FIFA World Cup 2014) and were obtained in each of the moments following samples: (i) at time I gave a sample of 347 participants; (Ii) upon II yielded a sample of 220 participants; and (iii) when III yielded a sample of 268 participants, the final sample of 835 participants. Data analysis was performed in two steps. The first step with a descriptive analysis of the data in order to determine the profile of the participants and the second stage included an exploratory factor analysis in order to verify the sets of factors that express common characteristics in motivating individuals with regard to the nonattendance to stadiums. The results of the analysis have identified common characteristics before and after the canopy and different characteristics during the World Cup. It is hoped that future studies be conducted in other regions in order to identify the variables that most affect the retail football matches consumption in Brazilian stadiums. It is hoped that this research not only meets the academic community, but also make it useful for managers and organizations linked to sport.